Load shuffling during creep deformation of an additively manufactured AlCuMnZr alloy. (1st January 2023) - Michi, Richard A.; Bahl, Sumit; Fancher, Christopher M.; Sisco, Kevin; Allard, Lawrence F.; An, Ke; Yu, Dunji; Dehoff, Ryan R.; Plotkowski, Alex; Shyam, Amit
Abstract: The high-temperature deformation behavior of an additively manufactured Al-Cu-Mn-Zr alloy is evaluated in the as-fabricated and heat-treated states using traditional ex-situ and in-situ neutron diffraction creep experiments performed at 300 °C. The dominant reinforcement phase in the alloy, θ-Al2 Cu, despite its high volume fraction of ∼10%, does not provide load transfer strengthening during creep deformation. Instead, the lattice strain evolution suggests a new mechanism we term "load shuffling" wherein the initial load is transferred away from precipitate-free zones along the grain boundaries where most of the θ-Al2 Cu particles are located to precipitate-strengthened grain interiors. Notwithstanding the lack of load transfer strengthening, the as-fabricated AM Al-Cu-Mn-Zr alloy still possesses improved creep resistance at 300 °C relative to a cast alloy with similar composition. The proposed load shuffling mechanism explains the lack of observed L12 -Al3 Zr strengthening at 300 °C and helps identify several strategies for improvement of elevated-temperature mechanical response of AM Al alloys. Graphical abstract: Image, graphical abstract